HALF-HEARTED POLITICAL PARTICIPATION: SOCIAL MEDIA AND FULFILMENT OF ISLAMIC YOUNG VOTERS’ INFORMATION NEED - Setiawan, Koesworo; Fahriza Permana, Muhammad (Politea : Jurnal Politik Islam, 2024)
Young people in Indonesia comprise a large population but are synonymous with low political participation. This study aims to determine social media's influence on Islamic young people's political participation. Respondents were selected from as many as 88 people through the Slovin formula from a population of 712 students. The independent variable is the content of messages in the @totalpolitikcom Instagram account with clear, convincing, concise, comprehensive, and concrete indicators. The dependent variable is the political attitude of students with cognitive, affective, and conative indicators. The pre-test results showed all instruments were valid and reliable. Measurement of the coefficient of determination showed a positive effect of variable x on variable y on level 78.4%. The questionnaire results showed that the “clear” indicator (x1) had the highest score, then “convincing” (x2) and the “conative” (y3) had the lowest. The study concluded that social media had a significant effect on political attitudes. However, the lowest scores of x2 and y3 indicate that social media messages failed to address respondents' primary concerns, resulting in half-hearted political participation.